Esophageal Squamous Cell Carcinoma Causing Nonbacterial Thrombotic Endocarditis - Nitish Batra; Sourya Acharya; Sunil Kumar; Samarth Shukla; Anusha Gupta (Journal of the Practice of Cardiovascular Sciences)
The illness known as nonbacterial thrombotic endocarditis (NBTE) is characterized by the deposition of fibrin and thrombi on deteriorated or normal heart valves without microbes. Compared to infective endocarditis, this disease is more frequently observed in chronic inflammatory conditions and is linked to a higher incidence of thromboembolic events. Vegetations on two-dimensional echocardiography and negative blood cultures suggest the disease. It is generally associated with advanced malignancies and very rarely with squamous cell carcinoma (SCC) of the esophagus. Here, we describe the case of a 68-year-old female with SCC of the esophagus who developed NBTE.